The role of Iranian medicinal plants in experimental surgical skin wound healing: An integrative review - Derakhshanfar, Amin (Iran J Basic Med Sci, 2019)
OBJECTIVE(S): Wounds are physical injuries that cause a disturbance in the normal skin anatomy and function. Also, it has a severe impact on the cost of health care. Wound healing in human and mammalian species is similar and contains a complex and dynamic process consisting of four phases for restoring skin cellular structures and tissue layers. Today, therapeutic approaches using herbal medicine have been considered. Although the benefits of herbal medicine are vast, some medicinal plants have been shown to have wound healing effects in different experimental studies. Therefore, the current review highlights information about the potency of herbal medicine in the experimental surgical skin wound healing. MATERIALS AND METHODS: Electronic database such as PubMed, Google Scholar, Scopus, and Medscape were searched for Iranian medicinal plants with healing activity in experimental surgical skin wounds. In this area, some of the most important papers were included. RESULTS: There are numerous Iranian medicinal plants with skin wound healing activity, but clinical application and manufacturing are very low in comparison to the research volume. CONCLUSION: In normal instances, the human/animal body usually can repair tissue damage precisely and completely; therefore, the utilization of herbs is limited to special conditions or in order to accelerate the healing process.